(untitled) (Journal Of Educational and Psychological Researches, 2020)
Abstract Type D personality leads the individuals to show resistance towards rehabilitation and wallow in depression and doubt. The main objective of this study is to investigate the effect of Type D-Personality in increasing the level of personality disorder. In order to achieve the main objective, 165 undergraduate students from a public university in Baghdad, Iraq have been selected to respond to two sets of questionnaires namely Type D-Personality (TDP) by Denollet & Colleagues (2011), as well as the International Personality Disorder Examination (IPDE) by Loranger (1994). The results showed that TDP has a significant effect on AVPD & DPD, whereas it has no significant effect on OCPD. Implications and limitations of the study were discussed, and suggestions for future research are offered. The danger of the TDP should be introduced as early as possible before young couples started to become students and get into university society.